The Agricultural Guarantee Program (PROAGRO) as an instrument for plant health defense in Brazil: The case of maize in the period 2015 to 2022 (Research, Society and Development, 2023)
Agriculture is an activity that presents the greatest production risks compared to other activities. This sector depends not only on the rational and efficient use of inputs such as fertilizers and pesticides, but also on market behavior, the proper use of technologies, and climatic and biotic conditions, such as pest and disease attacks. In the field of rural insurance, prevention and mitigation efforts aim to reduce the probability of adverse events and/or reduce the impact of events. Risk transfer is the process of redistributing the negative economic effects of an event between a group of actors. This process is the reason for the existence of agricultural insurance. In this context, government rural credit plays a fundamental role in the development and sustainability of the agricultural sector and is directly linked to the PROAGRO rural insurance program. This research aims to evaluate the use of the government rural insurance program called PROAGRO and its benefits and potentialities as a plant health protection tool, since it can cover possible occurrences associated with pest and disease attacks in Brazil. The focus will be on corn production in the period from 2015 to 2022. This research applied an exploratory data analysis approach. Bibliographic review and access to databases in printed and electronic media were used. The analysis of the data collected revealed a growing importance of events related to pest and disease attacks from 2015, showing that there is an important potential for using PROAGRO as a plant health protection tool in Brazilian agriculture.